Trajectory Tracking Control Study of a New Parallel Mechanism with Redundant Actuation. (11th January 2020) - Zhang, Haiqiang; Fang, Hairong; Zhang, Dan; Zou, Qi; Luo, Xueling
Abstract : Parallel mechanisms with redundant actuation are attracting numerous scholars' research interest due to their inherent advantages. In this paper, an efficient trajectory tracking control scheme for the new redundantly actuated parallel mechanism by integrating force/position hybrid control with the combination of inertia feed-forward control and back propagation (BP) neural network PID control is proposed. The dynamic models including the joint space and task space are formulated explicitly in efficient and compact form by means of the principle of virtual work and d'Alembert formulations. The force/position hybrid control is implemented to perform trajectory tracking and optimize the driving force configuration in MATLAB/Simulink environment, before being applied to an actual parallel mechanism. The illustrative simulation results demonstrate that the force/position hybrid control scheme is available to provide good trajectory tracking performance. Simultaneously, the feasibility of the proposed control scheme is verified by comparison analysis with the aforementioned conventional control method.